The mind of Thucydides - Romilly, Jacqueline de (Cornell studies in classical philology., 2012)
First published in France in 1956 and now available in English for the first time, this narratological analysis of Thucydides's ""History of the Peloponnesian War"" highlights the power and sophistication of the Greek historian's rhetoric.